Paradigma Baru dalam Konseling Pastoral bagi Transpuan - Twin Hosea Widodo Kristyanto; Rikardo P. Sianipar; Twin Yoshua Raharjo Destyanto (Sekolah Tinggi Teologi Internasional Harvest Tangerang, 2022)
Transwomen people need to be acknowledged and reached by the church. Transgender people need to be acknowledged and reached by the church. There is a bad stigma attached to them, for instance. Therefore, this paper aims to explain Jesus' counseling practices for Samaritan women and how they relate to transwomen's counseling needs. A qualitative method was used in this study, including literature analysis, narrative analysis of John 1:1-42, and phenomenology of RS sources (motivators of the transwomen prayer group). Based on the literature study and narrative research results, it appears Jesus counseled the Samaritan woman through several stages: acceptance, responding to rejection, recovery, evangelism, and being born again. According to the interview results, transwomen need counseling for acceptance, equal treatment, and religious freedom. Thus, it is concluded that Jesus' counseling praxis for Samaritan women in John 4:1-42 can be applied to transgender women. The counseling stages carried out by Jesus in the narrative can help transgender people receive acceptance, equality, and freedom of worship.